PEMBENTUKAN KARAKTER MELALUI MANAJEMEN PENDIDIKAN - Al Akhyar, Dwiki (Indonesian Journal of Islamic Studies (IJIS), 2025)
This study aims to assess the effectiveness of educational management in developing students' character. The research method employed is a survey, which involves collecting data through questionnaires distributed to students and teachers in selected schools. The sample consists of students and teachers from a specific vocational high school. The findings indicate that effective educational management has a significant positive impact on character development among students. Key factors such as school leadership, communication patterns between teachers and students, and support from the school environment play important roles in shaping character. The implications of this research highlight the importance of effective educational management in character formation and the crucial roles of school leaders and teachers in creating a conducive educational environment. These findings can serve as a reference for schools and educational stakeholders to enhance programs and activities aimed at improving students' character development. Overall, the research results regarding the effectiveness of educational management in character development provide important conclusions that are essential for advancing character education in Indonesia and improving the quality of school management.